2022
DOI: 10.3390/diagnostics12061303
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Acute Hepatic Porphyrias

Abstract: Background Acute hepatic porphyrias (AHPs) are a group of rare diseases caused by dysfunctions in the pathway of heme biosynthesis. Although acute neurovisceral attacks are the most dramatic manifestations, patients are at risk of developing long-term complications, several of which are of a vascular nature. The accumulation of non-porphyrin heme precursors is deemed to cause most clinical symptoms. Aim We measured the serum levels of endothelin-1 (ET-1) and nitric oxide (NO) to assess the presence of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…In the present study, we observed an increased risk of pregnancy‐induced hypertensive disorder in women with AHP, which is consistent with some previous reports 38,39 . Underlying mechanisms in terms of endothelial dysfunction have been suggested 40 . One previous Norwegian register‐based cohort study, 30 did not observe a clear correlation between AHP and pregnancy‐induced hypertensive disorder.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we observed an increased risk of pregnancy‐induced hypertensive disorder in women with AHP, which is consistent with some previous reports 38,39 . Underlying mechanisms in terms of endothelial dysfunction have been suggested 40 . One previous Norwegian register‐based cohort study, 30 did not observe a clear correlation between AHP and pregnancy‐induced hypertensive disorder.…”
Section: Discussionsupporting
confidence: 93%
“…38,39 Underlying mechanisms in terms of endothelial dysfunction have been suggested. 40 One previous Norwegian register-based cohort study, 30 did not observe a clear correlation between AHP and pregnancyinduced hypertensive disorder. Our observations are based on a larger group of women with AHP (214 vs. 90) during a more recent period (1987-2015 vs. 1967-2006) with a more updated diagnostic classification system.…”
Section: Interpretation and Comparison With Previous Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Mild haem protein deficiency during an attack has been demonstrated in the liver [ 15 , 19 ]. Significant alteration of NO level in addition to endothelin-1, has been demonstrated in symptomatic AHP patients, but the origin of this alteration is unclear [ 53 ]. The deficiency of haem-containing endothelial nitric oxide synthase (NOS) 1 in the brain has been assumed to be responsible for NO deficiency and cerebral vasoconstriction [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic peripheral sensitization reflects functional up-regulation of some sodium channels including Na v1.7, Na v1.8, and Na v1.9 on the free nerve endings. This could be elicited by proinflammatory mediators from the liver that are significantly elevated in AIP patients with recurrent attacks ( 58 , 59 ). Some mediators potentially induce glutamate-mediated activation of N-methyl D-aspartate receptors.…”
Section: Pathophysiology Of Painmentioning
confidence: 99%